Sport for Women Means Life - Irene Kamberidou (SPOTLIGHT, A Fortnightly Publication for Political Studies, Publication of the Institute of Political Studies (I.P.S), no. 13, Dec. 1, 1984: 8., 1984)
Kamberidou, Irene (1984). Sport for Women Means Life. SPOTLIGHT, A Fortnightly Publication for Political Studies, Publication of the Institute of Political Studies (I.P.S), no. 13, Dec. 1, 1984: 8.